Figurative Language Analysis in “Sing 2” Movie by Garth Jennings: A Semantics Study - Bintang Rizki Mukti; Deden Novan Setiawan Nugraha (Universitas Cokroaminoto Palopo, 2022)
This research aims to explain figurative language with meaning in Sing 2. This research used qualitative descriptive research methods. The theory used in this research is the theory of figurative language by X.J., Kennedy which states that there are eight types of figurative language such as metaphor, irony, simile, personification, hyperbole, allusion, metonymy, and symbol. The identification is done by looking at the dialogue that has been transcribed and analysing the figurative language in each dialogue based on literature: An introduction to Fiction, Poetry and Drama second edition by X.J., Kennedy. The result of this research there are four types of figurative languages, such as 12 metaphors (52,4%), 8 hyperboles (34,7%), 2 ironies (8,6%), and 1 symbol (4,3%). Metaphor commonly used in Sing 2 because the dialogue must make the audience used their critical thinking. Each figurative language in Sing 2 has non-literal meaning which makes the dialogue between characters have a different impression.